"Hate Me Now": An Instance of NAS as Hip-Hop’s Self-proclaimed Prophet and Messiah - Dube, Siphiwe Ignatius (Religious studies and theology, 2010)
This article analyses rapper NAS’ video entitled "Hate Me Now" as an instance of his broader self-perception/self-construction/self-affirmation/self-proclamation as the Messiah of hip-hop and a rap-prophet making proclamations on American socio-political and religious values. In particular, the article locates and evaluates the significance of the video within the broader context of the artist’s ambiguous negotiation of the relationship between religion(s) and hip-hop-explicitly rap music-that extends beyond the usual blues connection. The article makes the claim that through rap music and other aspects of hip-hop culture, certain hip-hop artists see themselves as performing the role that they believe religious leaders and politicians seem to have failed at fulfilling. In this sense, NAS’ soteriological self-portraiture in the video analysed in this essay, and his musical career in general, is more than simply metaphoric, but enters into the realm of the metonymic, thus opening up space for a reconfiguration of not only hip-hop as another source of a religious sensibility, but also of "religion" as another commodity in the diverse marketplace of worldviews that give meaning to our everyday reality.